GRAIN PROPERTIES OF NEW INBRED LINES IN COMPARISON WITH MAIZE HYBRIDS - Nikolić, Valentina (Journal on Processing and Energy in Agriculture, 2020)
Grain quality parameters of five new maize inbred lines were investigated and compared with the corresponding properties of two commercial hybrids used in flour production. Kernel of the line L2 had the highest 1000-kernel weight (267.54 g), and line L2 had the highest test weight (844.68 kg m-3). The milling response ranged from 9.80 (L2) to 14.03 s (L1). The largest share of the soft fraction of endosperm was determined in L3 (37.13 %), which is slightly lower than in hybrid ZP 633. The highest protein (12.37 %), as well as crude fibre content (2.59 %) was determined in inbred line L4, while the lowest protein was found in the line L2 (9.36 %), and the lowest crude fibre content (1.81 %) was detected in line L3. All tested maize inbred lines were found to be highly prospective for breeding of new hybrids with improved grain quality parameters.
Keywords: inbred lines, maize hybrids, chemical composition, physical traits, whole-grain maize flour